Zebrafish myo7aa affects congenital hearing by regulating Rho-GTPase signaling - Xie, Binling; Liang, Jiaxin; Jiang, Jifan; Zeng, Ting; Liu, Ling; Xie, Dinghua; Zhu, Ganghua; Xiong, Lei; Zhang, Kanjia; Liu, Dong; Gong, Jie; Chen, Xiangding; et al. (Frontiers in Molecular Neuroscience, 2024)
Introductionmyo7aa, the homolog of the human Usher 1B syndrome pathogenic gene, myo7A, plays an important role in stereociliary development and maintenance, therefore, is critical for hearing and balance. However, the molecular mechanisms that myo7aa regulate hearing and balance still need to be studied.MethodsIn this study, we generated two independent zebrafish myo7aa knockout lines using CRISPR/Cas9 technology. To investigate the effects of myo7aa on hearing, YO-PRO-1 staining and startle response assay were used. To gain insight into the specific molecular mechanisms by which myo7aa affects hearing, transcriptome sequencing and bioinformatics analysis were employed.ResultsOur study showed that hair cells of myo7aa-/- zebrafish can not take up YO-PRO-1 fluorescent dye and are insensitive to acoustic stimulation in myo7aa-/- zebrafish compared to wild type. Genes related to the Rho GTPase signaling pathway, such as arhgap33, dab2ip, and arghef40, are significantly down-regulated in myo7aa-/- zebrafish embryos at 3 dpf. GTP and ATP compensation can partially rescue the hair cell defects in myo7aa knockout zebrafish.DiscussionOur findings suggest that zebrafish myo7aa affects congenital hearing by regulating Rho GTPase signaling, and loss of myo7aa leads to abnormal Rho GTPase signaling and impairs hair cell function. myo7aa, myo7A, arhgap33, dab2ip, arghef40 and myo7aa-/- fonts in the abstract are italicized. -/- is a superscript format.